(3WhGSjf GdGRds - (3GdMSjf Hf efUhQ GdMdGL, CHh eZjK,J (B309 (3g` s
(3ChdgG (B:s
(3bGd GdMSjf Hf efUhQ GdMdGL WS WS GdSQGL SQGL ef fhQ GdZjH HOGhi hLGhR GdTQM hSGO s
(3BNQgG (B:s
(3hGdi Cf cGjdGJ ef GdLhGfH LhGfH GdGLGfH aHbi GdJhMjO heG hQGg cdgG MhGOK hGdSdGe JeJ GdWhGSjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B63s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(381) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs